Standar Kecantikan Maiko dalam Drama Maiko-San Chi No Makanai-San Karya Hirokazu Koreeda - Ismawati, Trisna Rahma; Sulatri, Ni Luh Putu Ari; Artana, I Nyoman Rauh (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 7 No 1 (2025), 2025)
This research is titled “Maiko Beauty Standards in Hirokazu Koreeda's Drama Maiko-san Chi no Makanai-san”. This research aims to find out the representation of maiko beauty standards and their meanings displayed through the physical appearance of maiko. In the data collection stage, the listening method with note-taking technique was used. In the data analysis stage, the descriptive analysis method is used and in the presentation stage of the research results, the informal presentation method is used. The theories used in this research are literary anthropology theory and Barthes semiotics theory. Based on the analysis, it is known that maiko beauty standards contain the concept of traditional beauty of Japanese women. Wareshinobu, ofuku, and yakko-shimada hairstyles are hairstyles with a high level of complexity and are decorated by kanzashi or crowded hair ornaments on the maiko's head. White makeup or oshiroi is used all over the face by the maiko to give a perfect look. Red face makeup or kyobeni is also used by maiko to give the face a bright and not pale look. There were also clothes used by maiko in the form of hikizuri kimono, darari obi, okobo, and tabi. In addition, there is also the use of kago or traditional handbags by maiko as a fashion accessory as well as making it easier for her to carry the items needed when working. The representation of maiko beauty standards displayed through hairstyles, makeup, and clothing contains meanings that support traditional Japanese women's beauty. The maiko beauty standard refers to a self-identity that is feminine, graceful, elegant, neat, and luxurious.